2022
DOI: 10.3389/fmed.2022.843074
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Cell-Based Inflammatory Markers as a Useful Tool for Early Diagnosis in Colorectal Cancer

Abstract: BackgroundSystemic inflammation seems to be involved in the pathogenetic pathways of colorectal cancer (CRC). Analytical markers that reflect the inflammatory status, such as neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR) or systemic immune-inflammation index (SII), have been proposed as tools for the prognosis of CRC. Nevertheless, their use for diagnosis has been scarcely investigated.AimsTo analyze the ability of these markers and of a new marker combining SII and hemoglobin concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Recently, increasing attention has been paid to peripheral blood inflammatory markers and their usefulness in establishing prognosis in different diseases, such as cervical cancer, colorectal cancer, psychiatric disorders, and infections [4,[6][7][8][9]. Neutrophil-lymphocyte ratio and SII were shown to be prognostic markers for malignancies and inflammatory conditions [4,[6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing attention has been paid to peripheral blood inflammatory markers and their usefulness in establishing prognosis in different diseases, such as cervical cancer, colorectal cancer, psychiatric disorders, and infections [4,[6][7][8][9]. Neutrophil-lymphocyte ratio and SII were shown to be prognostic markers for malignancies and inflammatory conditions [4,[6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The burn-induced inflammatory process is very complex. The balance between all inflammatory mediators can be analytically reflected by the blood levels of PLT and leukocytes, especially neutrophils and lymphocytes [8]. Neutrophils and monocytes play a crucial role in the initial inflammatory phase [10].…”
Section: Discussionmentioning
confidence: 99%
“… 43 Systemic inflammatory cell ratios could be useful in early diagnosis of CRC. 44 NRL and PLR are useful markers in diagnostic and early recognition of different stages of CRC. 45 Monocyte‐to‐lymphocyte ratio (MLR), NLR and PLR are valuable predictive markers of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fibrinogen to pre‐albumin ratio is a biomarker for diagnosis of CRC 43 . Systemic inflammatory cell ratios could be useful in early diagnosis of CRC 44 . NRL and PLR are useful markers in diagnostic and early recognition of different stages of CRC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes can weaken tumor immune monitoring by inducing cytotoxicity and further reducing the host's antitumor immunity. 62 , 63 Emir et al 64 found that preoperative NLR and preoperative platelet-to-lymphocyte ratio (PLR) could be used as markers to monitor the progression of adenomatous polyps to aggressive tumors, indicating that the higher NLR and PLR values, the greater the carcinogenesis risk.…”
Section: Relationship Between Intestinal Immune Microenvironment and ...mentioning
confidence: 99%